The role of maternal attachment in mental health and dyadic relationships in war trauma. Issue 12 (December 2019) - Punamäki, Raija-Leena; Qouta, Samir R.; Diab, Safwat Y.
Abstract: Background: Infant care is a demanding task in dangerous war conditions, but research on the wellbeing of mother-infant dyads is mainly available in peaceful conditions. Knowledge on protective versus risking processes is especially vital for tailoring effective help, and the present study proposes the maternal attachment style to play an important role in dangerous war conditions. Objective: The study analyses, first, how various traumatic war events, such as losses, horrors and life-threat, are associated with maternal mental health and dyadic mother-infant interaction quality, indicated by maternal emotional availability (EA). Second, it tests a hypothesis that maternal insecure attachment risks and secure attachment protects good mental health and optimal EA from negative impacts of traumatic war events. Method: The prospective three-wave study involved 502 Palestinian mothers, who were pregnant during the 2014 War on Gaza, and participated at delivery (T1), and when the infant was seven (T2; N = 392) and eighteen (T3; N = 386) months. Mothers reported about war events at T1 and T2 (death and losses, witnessing horrors and life-threat), and posttraumatic stress disorder (PTSD) and depression symptoms at T2 and T3. Dyadic interaction quality was assessed by mother-perceived emotional availability (EA) scale at T2 and T3, and attachment styles by mothers' self-reports at T3. Results: Death and losses, witnessing horrors, and life-threat were all associated with a high level of maternal PTSD, but only at T2, whereas death and losses were associated with her depressive symptoms both at T2 and T3. Witnessing horrors was associated with a low close and positive and a high distant and negative emotional availability at T2 and T3. As hypothesized, maternal avoidant attachment was associated with a low level of close and positive EA in general, and especially when the dyads were exposed to a high level of traumatic war events, thus indicating a risking function. Against the hypothesis, secure attachment did not show any protective function on emotional availability, while, unexpectedly, maternal preoccupied attachment was associated with close and positive emotional availability, when dyads were exposed to a high level of traumatic war events. Conclusion: Mothering in conditions of war and military violence is an overwhelmingly demanding task, and mother-infant dyads need legal, social, and psychological assistance. Knowledge and reflection of unique responses and meanings of different attachment styles would be fruitful in tailoring effective help. Abstract : Psychology; Sociology; Clinical psychology; Mental health; Child development; Personality; Well-being; War trauma; PTSD; Depression; Pre- and postnatal period; Mother-infant dyadic interaction; Emotional availability; Attachment styles